Assessment of Secondary School Teachers’ Utilization of Internet Facilities For Instruction In Ilorin, Nigeria - Janet Adenike Aderogba (IJER (Indonesian Journal of Educational Research), 2020)
Computer is an indispensable component of our day to day lives in the present technological era. The development of practical skills and knowledge of computers is, naturally, very important as well. Internet is the design and development of computer-based information system that deals with the use of electronic computers and computer software to convert, store, process, transmit and retrieve information, browse or surf. The objectives of this study were to: identify Internet facilities available for secondary school teachers; determine whether secondary school teachers are able to utilize the Internet facilities; and investigate how teachers’ gender influence the utilization of internet facilities in secondary schools in Ilorin. The population of the study was limited to secondary school teachers in Ilorin, Nigeria. Two hundred and fifty one (251) respondents were randomly selected from the eighteen secondary schools in Ilorin, Nigeria. A structured questionnaire was drawn and administered on the teachers. Reliability coefficient of 0.89 was realized when the questionnaire were administered on twenty five (25) secondary school teachers in Ogbomoso, Oyo State, using cronbach’s alpha. The research questions were answered using mean, while t-test statistic was used to test the two hypotheses. Findings of the study revealed that there was no significant difference between male and female teachers’ level of utilization of internet facilities for instruction. The study concluded that teachers utilize the available internet facilities for instruction. It was recommended that, Teachers should be encouraged to utilize internet facilities to prepare their lesson plan.